PELATIHAN PEMANFAATAN LIMBAH PERTANIAN SEBAGAI PUPUK ORGANIK DI KELURAHAN KALAMPANGAN KECAMATAN SEBANGAU KOTA PALANGKA RAYA - Zubaidah, Siti; Sustiyah; Rahayuningsih, Sri Endang Agustina; Sulistiyanto, Yustinus (Jurnal Pengabdian Kampus, 2024)
Kalampangan Village is known as a transmigration area that has advanced in the agricultural sector, especially vegetable crops and is the largest supplier of vegetables in Palangka Raya City. One effort to increase peat soil fertility is through fertilization. So far, fertilization has mostly used inorganic fertilizers. Excessive inorganic fertilizer can disrupt soil health, besides being expensive and sometimes rare on the market. Farmers now cannot clear land by burning it, so that the resulting weeds pile up around the land. At harvest time, a lot of harvest waste is not utilized optimally. So far, it has only been buried in the ground fresh as green manure and animal feed.  One effort to overcome the problem of accumulated weeds and crop residue is to make organic fertilizer (compost). Compost contains nutrients that plants need and is able to repair soil structure damaged by too much inorganic fertilizer. The objectives of the activity are: 1) Utilizing agricultural waste as organic fertilizer; 2). Providing skills in making quality organic fertilizer. The method used is counseling and training in making organic fertilizer.   The extension and training activities were attended by 10 members of the farmer group. Training on making compost was carried out using broadleaf weeds and sweet corn harvest waste. Composting is carried out for 3 weeks to 1 month. The characteristics of compost that is ready to use are blackish brown color, crumb structure, coolness and compost aroma. The compost produced is of sufficient quality with the nutrient content N, P and K meeting organic fertilizer quality standards. Farmers are very enthusiastic about making compost and hope that later it can be applied in growing vegetables in Kalampangan Village.